OPPORTUNISTIC MICROORGANISMS IN RHEUMATIC DISEASES - M. Yu. Gulneva; S. M. Noskov; E. V. Malafeeva (Научно-практическая ревматология)
The paper gives the data available in the literature on the role of opportunistic microorganisms (OMs) in rheumatic diseases (RDs). OMs are anticipated to be involved as triggers initiating the development of chronic inflammation. Along with this, OMs in autoimmune diseases may play a defensive role through the interaction with Toll-like receptors and the activation of T cells that have suppressor activity. The possible involvement of OMs in the pathogenesis of RDs provides support not only the isolation of microorganisms, but also the detection of antibacterial antibodies of different classes. Of great importance are OMs in the etiology of comorbid infections, the risk of which is due to both the presence of autoimmune RDs and the necessity of using the drugs having immunosuppressive activity. The active clinical introduction of biological agents is followed by a rise in the rate and severity of different infections, including those caused by OMs. Having a marked biological and environmental plasticity, OMs are able to persist long when there are changes in the immune defense of patients with RDs. There is evidence for the higher adhesive properties and persistent potential of the microorganisms that colonize the body of patients with RDs. In the latter, OMs that are distinguished by pronounced antibiotic polyresistance are isolated, making the treatment and prevention of opportunistic infections more difficult in rheumatology. The results of the papers analyzed in the review suggest that the study of OMs in RDs is of practical importance.